Effectiveness of Charismatic Leadership of Madrasah Principal in Improving Teacher Performance Mas - Wahyu Darmawan; Nasution, Inom; Nurika Khalila Daulay (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This research was conducted because every teacher is able to follow the program that is the goal of education in improving the quality of students. Described through the achievements that have been achieved by students.  And this is inseparable from the leadership style of the madrasah head. This study uses a qualitative research design with an ethnographic approach focusing on social research. Researchers go directly to the field of data collection techniques, namely interviews, observation and documentation. Regarding data analysis, the author uses techniques, namely data reduction, data display, and conclusions.Data validity techniques with data triangulation. Validation is done by comparing statements from other parties. The principal of MAS Darul Amin madrasah in improving teacher performance through various well-structured programs with teachers and significant efforts. The madrasah head's contribution is designed to meet all the necessary needs of the teachers. The principal of Darul Amin madrasah makes every effort to ensure that quality improvement programs are optimally implemented, addressing not only those aspects managed by individual teachers but also the entire school system. These efforts include innovative strategies and systemic reforms that integrate all aspects of the education environment. By addressing these challenges through ongoing dialogue and collaborative problem-solving, the madrasah can develop an adaptive and resilient education program. The madrasah head plays a critical role in ensuring the effectiveness of all communication processes within the institution.